Scientists discover what makes locusts swarm - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
A chemical sometimes found in the foam that surrounds locust eggs could provide a key to locust control. The chemical is responsible for the young turning into gregarious locusts: when the chemical is not present, locusts will hatch as solitary...